Analisis Location Quotient dalam Penentuan Produk Unggulan pada Beberapa Sektor di Kabupaten Lingga Kepulauan Riau - Ely Kartikaningdyah (Politeknik Negeri Batam, 2012)
To develop the economic potential of new areas need to be assessed what the potential winning by identifying available resources in order to increase the community's economy and develop the agriculture sector, plantation, animal husbandry, fisheries, forestry and processing industry. In this study examines the potential of winning a region by using analysis of Location Quotient (LQ) in each sub-region to find a superior product that can be developed and revenue potential. Of a superior product that is known, the government will be meyusun program as pengembanga plan area. Districts that are identified in the District Linga is on 5 (five) districts are linga, North Linga, Singkep, West Singkep and Senayang. Research using quantitative descriptive analysis method and data collection of primary data - secondary with the observation, interview, FGD and deployment questionnaire. The results showed that of the five districts each district has a potential that varies according to demographic, cultural, regional conditions, the infrastructure and resources already available that could be developed as a superior product. The results of calculation of LQ, the sectors in the district court that Linga is the potential to be developed in the agricultural sector LQ of 0.91, mining and quarrying, transport and communication with the LQ of 1.5, finance, leasing and services company with a LQ of 1, 06 and the services sector with a LQ of 1.17 is the calculated average LQ is above 1. In the District Linga is the superior product in the agricultural sector (crops, fruits and vegetables), sub-district of North Linga is the livestock sector (cattle and goats), District Singkep the plantation sector (coconut, rubber, pepper), District of West Singkep plantations (oil palm and rubber), District Senayang are marine capture fisheries and aquaculture sea and ocean, while freshwater aquaculture in the Northern District of Linga and Linga which synergized with the development of the agricultural sector. Types of commodities are the types of grouper, red fish, mackerel udag, sengarat, machetes, sagai, ranjungan, pomfret, trevally, anchovy, kurau, squid, etc.. Marine aquaculture in the form ofseaweed, while the cultivation of freshwater cat fish.